On-chip non-volatile reconfigurable THz varifocal metalens - Zhang, Shoujun (2024)
Implementation of integrated, nonvolatile, and reconfigurable solutions for on-chip terahertz (THz) metadevices holds great potential for applications in sensing, integrated circuits, and high-speed communications. This study demonstrates the non-volatile reconfigurable dynamic manipulation of THz on-chip metadevices through optical modulation of Ge2Sb2Te5 (GST) and 2π phase shift of metasurfaces. The approach allows for the simultaneous realization of surface plasmons (SPs) excitation, wavefront shaping, and amplitude modulation in a single device. Using the principles of 2D holography, a reconfigurable multilevel THz SP metalens switch with a maximum extinction ratio of 29.9 dB is presented. The focusing intensity of the metalens can be continuously modulated by varying the pump laser energy. The implementation of the approach is further demonstrated by realizing a switchable THz SP varifocal metalens. Reconfigurable, reversible, and repeated switching is achieved through optical and thermal stimuli, resulting in switching contrast ratios of 7.4 dB and −44.4 dB in the amorphous and crystalline states of GST, respectively. The results demonstrate a promising route toward developing non-volatile, reconfigurable, and energy-efficient on-chip THz integrated metadevices. By enabling the dynamic manipulation of THz waves on a single chip, the approach holds significant potential for advancing the field of terahertz-integrated photonics.